Major depressive disorder in veterans : antidepressant use and suicide prevention - Barton, Casey P. (Military and veteran issues., 2015)
In 2013, the Department of Veterans Affairs (VA) estimated that about 1.5 million veterans required mental health care, including services for Major Depressive Disorder (MDD). MDD is a debilitating mental illness related to reduced quality of life and productivity, and increased risk for suicide. VA also plays a role in suicide prevention. This book begins with a brief overview of the public health framework for suicide prevention, which forms the basis for both the National Strategy for Suicide Prevention and the VHA's approach to suicide prevention. The book discusses suicide surveillance; s.